1996
DOI: 10.1007/bf02245608
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical evidence for antagonism by olanzapine of dopamine, serotonin, α1-adrenergic and muscarinic receptors in vivo in rats

Abstract: The ability of the atypical antipsychotic drug candidate olanzapine to antagonize dopamine, serotonin, alpha-adrenergic and muscarinic receptors in vivo was assessed by various neurochemical measurements in rat brain. Olanzapine increased the concentrations of the dopamine metabolites DOPAC and HVA in striatum and nucleus accumbens. Olanzapine antagonized the pergolide-induced decrease of striatal DOPA concentrations in rats treated with gammabutyrolactone and NSD1015 and increased striatal 3-methoxytyramine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 28 publications
5
71
1
3
Order By: Relevance
“…However, the estimates we have made of the effective in vivo dissociation constant K d Ј (1.5 nM to 2.8 nM) agree fairly well with the low range of K i values (1.9 nM to 2.5 nM) found by Bymaster et al (1996a). In another study by the same group, treatment with olanzapine also resulted in an inhibition of ex vivo binding of [H-3]pirenzepine, (Bymaster et al 1996b). Yet, unpublished experiments by this group suggest that the previous study may have overestimated the affinity of olanzapine to the muscarinic receptor and that the true affinity may be 10-fold weaker .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the estimates we have made of the effective in vivo dissociation constant K d Ј (1.5 nM to 2.8 nM) agree fairly well with the low range of K i values (1.9 nM to 2.5 nM) found by Bymaster et al (1996a). In another study by the same group, treatment with olanzapine also resulted in an inhibition of ex vivo binding of [H-3]pirenzepine, (Bymaster et al 1996b). Yet, unpublished experiments by this group suggest that the previous study may have overestimated the affinity of olanzapine to the muscarinic receptor and that the true affinity may be 10-fold weaker .…”
Section: Discussionsupporting
confidence: 81%
“…In vitro , olanzapine antagonizes various dopamine, serotonin, histamine, norepinephrine and muscarinic receptors. The in vitro K i values for the muscarinic receptor subtypes range between 2 and 25 nM, similar to the K i value of 11 nM for olanzapine at the dopamine D 2 receptor (Bymaster et al 1996b).…”
supporting
confidence: 64%
“…The HAL dose (2.0 mg/kg/ day) was selected based on previous studies where this dose was found to establish clinically relevant (Baldessarini et al, 1988) steady-state plasma levels in the rat . This dose is also comparable to the optimal dose to cause pharmacological effects (Skarsfeldt, 1996;Didriksen, 1995;Bymaster et al, 1996). The schedule of HAL administration was selected based on several studies by us and others in which differences in behavioral as well as pharmacological effects were seen after 45 days of treatment in rats (Parikh et al, 2004a, b, c;Terry et al, 2004;Pillai et al, 2005;Angelucci et al, 2000;Dawson et al, 2001).…”
Section: Drug Treatments In Ratsmentioning
confidence: 99%
“…These data are further supported by Chengappa et al, 10 who suggest that olanzapine in vivo (patient-reported adverse events) is much less anticholinergic than would have been predicted from the originally published in vitro data. 2,6,11 The objective of the present analysis was to characterize the extent of olanzapine's in vivo anticholinergic activity by comparing solicited anticholinergic treatmentemergent adverse events as reported in a randomized, double-blind clinical trial of olanzapine and risperidone in patients not taking adjunctive anticholinergic medication. Risperidone was specifically selected owing to the expectation, based on in vitro assay data, that this commonly used agent had very low in vivo (in humans) affinity for muscarinic receptors.…”
Section: Objectivementioning
confidence: 99%
“…Risperidone was specifically selected owing to the expectation, based on in vitro assay data, that this commonly used agent had very low in vivo (in humans) affinity for muscarinic receptors. 6,11 The hypothesis tested was whether olanzapine and risperidone differed substantially in clinical, peripheral, anticholinergic-associated adverse events as indexed by the Association de Méthodologie et de Documentation en Psychiatrie (AMDP-5)-solicited adverse event symptom list.…”
Section: Objectivementioning
confidence: 99%